PEMERINTAH DAERAH DALAM DINAMIKA PEREKONOMIAN MASYARAKAT: PERSPEKTIF HUKUM DAN SOSIOLOGI: Local Government in The Dynamics of The Commuity Economy: A Legal and Sociological Perspective - Ajeng Permana; Aji Mulyana; Mia Amalia (Dialogia Iuridica, 2024)
This research highlights the long-term impact of economic events such as the 1990 crisis and the impact of the Covid-19 pandemic, emphasising the important role of government and community participation in managing an economy that still lacks synergy. This research aims to provide a better understanding of the role of local government in the economic dynamics of the community as well as the importance of community participation in economic development. The research method used is a document study with a qualitative approach. Data was obtained from various sources, including relevant laws and regulations, journals and reports. The qualitative approach allows an in-depth understanding of individual views on the issue under study. Local governments have great authority in managing economic resources in their regions, including budget management and development infrastructure, in accordance with Law No. 9/2015 on the Second Amendment to Law No. 23/2014 on Regional Government. However, local government intervention in the economy can also create new dynamics in the social structure and affect the distribution of wealth. Prudent economic policies from the government play a crucial role in economic development, through the creation of policies that support investment, incentives for the development of small and medium enterprises, and the provision of infrastructure that supports economic growth in the region. The importance of community participation and the implementation of policies that support regional autonomy are key to building an inclusive and sustainable economy.